Epidemiology of lung cancer in Eastern India with focus on histopathological subtypes and smoking history: a single rural tertiary center experience - Banerjee, Sanatan; Bhattacharya, Biswamit; Perumondla, Madhusudan (International Journal of Advances in Medicine, 2021)
Background: Lung cancer is the most common cancer and the leading cause of mortality worldwide. Smoking remains the commonest risk factor for development of lung cancer. This study aimed to evaluate the histopathological subtypes and smoking history among patients with lung cancer. Methods: This was a retrospective observational study that included all the patients attending Radiotherapy OPD of Burdwan Medical College during 2017 and 2018. Demographic data, smoking history, comorbidities, symptoms, smoking history, histology of lung cancer, stage at presentation, site of metastasis, and site of lesions were collected. Results: There were 484 patients, with a median age of 59 years, of which 82.4% were men and 17.6% were women. The men-to-women ratio was 4.7:1. Regular smoking was common in patients with lung cancer (72.7%). Total 12.4% of patients had small-cell carcinoma; of the 87.6% patients with non-small-cell carcinoma, the most common histology was adenocarcinoma (44.6%), followed by squamous cell (38.4%), large cell (17.0%). The most common metastatic sites were lung (42.1%) followed by bone (34.1%), lymph node (15.9%), liver (2.7%), vertebra (2.5%), pleura (2.1%), and anterior chest wall (0.6%). A larger proportion of men (92.6%) were smokers as compared women. There was a statistically higher occurrence of adenocarcinoma in smokers than in non-smokers (62.2% vs. 2.4%; p<0.001). The majority of patients with a smoking history (73.0%) were found to have advanced cancer (Stage IV). Conclusions: The present study confirmed that apart from smoking history, demographic characteristics appear to have an impact on lung cancer development.